Study on the application of progressive training method combined with imagery training method in laparoscopic suturing skills training for resident physicians - Wenxue Lin; Jian Yu; Xiaoping Peng; Jianfu Xia; Bingchen Huang; Rizeng Li (BMC Medical Education)
Abstract Objective This study aims to explore an efficient teaching method to improve laparoscopic suturing skills in resident physicians by combining the progressive training method with the imagery training method. Methods This study used a randomized controlled trial methodology. The experimental group received training utilizing a combination of the progressive training method and the imagery training method In contrast, the control group followed the traditional teaching method of practicing continuous complete actions. Both groups were trained in intracorporeal suturing and knot-tying under laparoscopy. The training effects of the two groups were compared and analyzed before and after the training, including LS-CAT scores and suturing time. Results In the second test, the experimental group had much higher LS-CAT scores than the control group, as well as a considerably lower number of operation errors. In the experimental group, 88.9% of the trainees were proficient, compared to only 28.6% in the control group. There was no significant difference in suturing time between the two groups. The results of the third test indicated that, although there were no significant differences in LS-CAT total scores or suturing time between the two groups, the experimental group demonstrated a significantly lower number of operational errors compared to the control group. Additionally, the LS-CAT scores for tissue handling in the experimental group were significantly better than those in the control group. Conclusion The combination of the progressive training method and the imagery training method significantly improved resident physicians’ laparoscopic suturing skills. This method greatly enhanced the efficiency and quality of learning laparoscopic suturing and knot-tying skills among surgical and gynecological resident doctors.